Composition Shift Due To Phase Hold-up in Two Phase Flow For Multicomponent Mixed-refrigerant - 公茂琼 (Zhileng xuebao)
The phase holdup caused by the velocity difference in the two-phase flow is one of the most important reasons for the composition shift of multicomponent mixtures.A model for calculating the composition shift was described.The Palmer modified Beggs-Brill-Moody correlation was employed in the calculation.With this model,influences of pipe angle and fluid temperature on the composition shift were discussed.The results show that the increase of the angle affects the hold-up obviously and then the composition shift varies greatly.The variation of the mixture concentration only occurs in the two-phase region and the concentration variation of different compositions changes with the temperature.